Building Digital Competence among Elementary School Teachers Throughb Training in The Design of Augmented Reality (AR) and Artifial Intelegency (AI) Enhanced Learning Media - Eryuni Ramdhayani Eryuni; Musahrain; Ade Safitri; Noviola Cabrini Santosa (Unram Journal of Community Service, 2025)
This Community Service Program (PKM) focused on enhancing the digital competencies of elementary school teachers through training in the development of learning media assisted by augmented reality (AR) and artificial intelligence (AI) technologies. The objective of this program was to strengthen teachers’ digital skills by providing both theoretical and practical training, accompanied by continuous evaluation. The service-learning approach was employed, covering socialization, workshops, hands-on practice, and evaluation. The evaluation results revealed that most teachers experienced significant improvement in designing and creating AR- and AI-assisted learning media. Moreover, their ability to operate and apply AR and AI tools increased substantially. Teachers were also able to produce innovative digital learning products and became more confident in integrating technology into their classrooms. Another notable outcome of this program was the establishment of a teachers’ learning community as a sustainable platform for further developing AR- and AI-assisted learning media. Overall, the findings demonstrate that the PKM activities had a positive impact by increasing teachers’ competencies in developing AR- and AI-based learning media that can be implemented in the teaching and learning process.